2010
DOI: 10.1182/blood-2010-01-261206
|View full text |Cite
|
Sign up to set email alerts
|

Platelet CD40L mediates thrombotic and inflammatory processes in atherosclerosis

Abstract: CD40 ligand (CD40L), identified as a costimulatory molecule expressed on T cells, is also expressed and functional on platelets. We investigated the thrombotic and inflammatory contributions of platelet CD40L in atherosclerosis. Although CD40L-deficient (Cd40l ؊/؊ ) platelets exhibited impaired platelet aggregation and thrombus stability, the effects of platelet CD40L on inflammatory processes in atherosclerosis were more remarkable. Repeated injections of activated Cd40l ؊/؊ platelets into Apoe ؊/؊ mice stron… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
225
1
4

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
1
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 260 publications
(232 citation statements)
references
References 55 publications
2
225
1
4
Order By: Relevance
“…38 On the contrary, activated platelets expressing CD154 were found to promote atherogenesis and inflammation by inhibiting the recruitment of Tregs. 39 Therefore, it is important to clarify the cell intrinsic role of CD154 in Treg induction. In our study, we showed that CD154 on platelets directly inhibits the induction of Tregs both in vitro and in vivo, providing a mechanistic explanation for the promotion of inflammatory responses and disease progression by CD154.…”
Section: Discussionmentioning
confidence: 99%
“…38 On the contrary, activated platelets expressing CD154 were found to promote atherogenesis and inflammation by inhibiting the recruitment of Tregs. 39 Therefore, it is important to clarify the cell intrinsic role of CD154 in Treg induction. In our study, we showed that CD154 on platelets directly inhibits the induction of Tregs both in vitro and in vivo, providing a mechanistic explanation for the promotion of inflammatory responses and disease progression by CD154.…”
Section: Discussionmentioning
confidence: 99%
“…Notably, however, the main receptors facilitating PLAs (i.e. P-selectin, CD40L, GPIbα, GPVI, GPIIb/IIIa on platelets and PSGL-1, CD40, Mac-1 on leukocytes) are consistently involved in both mice and human (2,4,6,8,3138). …”
Section: Translational Aspects Of Animal Modelsmentioning
confidence: 99%
“…Platelet activation and concomitant degranulation enables platelets to engage with leukocytes via soluble factors and physical interaction facilitated by a variety of receptors (1). Most importantly receptors involved in direct interactions include platelet P-selectin (CD62P) and CD40 ligand (CD40L), as well as PSGL-1, CD40 and Mac-1 (integrin α M β 2 , CD11b/CD18) on leukocytes (24). Platelet-leukocyte interactions are further stabilised by crosstalk of numerous additional receptor/ligand pairs that were reviewed previously (1,5) and trigger mutual activation and release of granular content by both platelets and leukocytes, thereby modulating leukocyte function and fine-tuning immune responses (5).…”
Section: Introductionmentioning
confidence: 99%
“…Platelet CD40L and endothelial cell CD40 interaction amplifies the release of IL-8 and MCP-1 from endothelial cells and enhances the expression of endothelial cell adhesion receptors including E-selectin, VCAM-1, and ICAM-1 . In vivo study using mice deficient of platelet CD40L shows that platelet CD40L accelerate plaque formation and progression, mainly due to prevention of leukocyte recruitment (Lievens et al, 2010). This study implicates that platelet CD40L is important for recruitment of monocytes, neutrophils and lymphocytes during plaque intitiation and progression.…”
Section: Tight Adhesion Of Platelet To Endothelial Cell Surfacementioning
confidence: 83%